Ischaemic mitral regurgitation: incidence, clinical and angiographic characteristics of 1000 patients with type 1 myocardial infarction undergoing percutaneous coronary intervention. (25th November 2020) - Sharma, H; Radhakrishnan, A; Brown, S; May, J; Zia, N; Joshi, R; Ludman, P.F; Townend, J.N; Doshi, S.N; Khan, S.Q; Zaphiriou, A; George, S; et al.
Abstract: Background: Previous studies of the incidence and severity of mitral regurgitation (MR) following acute myocardial infarction (MI) were limited by the study population (ST-elevation MI only), by diagnostic methods (lack of multiparametric quantification), or by the time-frame of study (late assessment post-MI). The true incidence of ischaemic MR (IMR) immediately following type 1 MI [non-ST-elevation (NSTEMI) and ST-elevation (STEMI)] patients in the modern era of universal early revascularisation remains unclear. Since even mild IMR confers a poor prognosis, factors which promote or protect against the development of MR require further evaluation. Purpose: To determine the incidence, clinical and angiographic characteristics of patients with IMR following type 1 MI treated with PCI. Methods: This was a single-centre study of 1000 consecutive, prospectively recruited patients admitted to the Queen Elizabeth Hospital Birmingham with type 1 MI who underwent PCI. Early inpatient transthoracic echocardiography (TTE) was performed by accredited echocardiographers using standard multiparametric quantification. Results: MR was observed in 294/1000 patients (29.4%) post-MI, graded as mild (76%), moderate (21%) and severe (3%). Median time from symptom onset to PCI was 1 day (IQR 0–4) and to TTE 2 days (IQR 1–3). Compared to patients without MR (MR-), those with MR (MR+) were older (73±12 years vs 66±13 years; p<0.001), male (75% vs 64%; p<0.001) and more likely to have a history of hypertension (HTN) (63% vs 55%; p=0.0117), heart failure (HF) (3.4% vs 1.1%; p=0.0140) and previous MI (28% vs 20%; p<0.005). MR+ patients more frequently presented with HF (8.5% vs 4.2%; p=0.0075), lower LV ejection fraction (LVEF) (50±14% vs 55±11%; p<0.001) and higher peak high sensitivity troponin T (765ng/L, IQR 170–3032 vs 400ng/L, IQR 51–1966; p<0.0001). MR+ patients were more likely to have severe disease in the left circumflex (LCx) (50% vs 33%; p<0.0001) or right coronary artery (RCA) (51% vs 43%; p=0.0135). Incidence of severe disease in the left main stem and left anterior descending artery (LAD) did not significantly differ between the two groups. Incidence of MR was equal (29%) amongst STEMI (126/431) and NSTEMI (168/569) patients. While the time to revascularisation did not affect the prevalence of MR following STEMI (linear regression analysis of door-to-balloon time in MR+ and MR- patients p=0.843), NSTEMI patients were more likely to develop MR if revascularisation was delayed (linear regression analysis of symptom onset to PCI time MR+ vs MR- p=0.061). Conclusion: Almost 1/3 of patients with type 1 MI undergoing revascularisation have MR evident on pre-discharge TTE. Factors promoting MR include older age, male sex, HTN, HF, larger non-LAD territory infarct, and depressed LVEF. The incidence of MR following STEMIs and NSTEMIs is equal. Earlier revascularisation is unlikely to reduce MR in STEMI patients but may improve MR prevalence following NSTEMI. Funding Acknowledgement: Type of funding source: None